2010
DOI: 10.1038/icb.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis impairs dendritic cell response by altering CD1b, DC‐SIGN and MR profile

Abstract: During a chronic infection such as tuberculosis, the pool of tissue dendritic cells (DC) must be renewed by recruitment of both circulating DC progenitors and monocytes (Mo). However, the microenvironment of the inflammatory site affects Mo differentiation. As DC are critical for initiating a Mycobacterium tuberculosis-specific T-cell response, we argue that interference of M. tuberculosis with a correct DC generation would signify a mechanism of immune evasion. In this study, we showed that early interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 49 publications
3
44
0
3
Order By: Relevance
“…2); thereby the numbers of DCs derived from both Mo subsets were adjusted for functional analysis. This higher tendency of the CD16 + Mo subset to cell death has also been observed when CD16 + Mos were differentiated into M s [45] supports our conclusion that CD16 + Mos have a more activated phenotype.The relevance of the lack of CD1 molecules displayed by DCs derived from CD16 + Mos was supported by the association between the lower CD1b expression on DCs with their declined ability to present Mtb Ags [21]. In this line, it has been demonstrated that CD1-restricted T cells are expanded in TST + HSs and that CD1-restricted T-cell responses are absent or drastically reduced in TB patients [46], indicating an helpful role of CD1 molecules during Mtb infection.…”
supporting
confidence: 51%
See 4 more Smart Citations
“…2); thereby the numbers of DCs derived from both Mo subsets were adjusted for functional analysis. This higher tendency of the CD16 + Mo subset to cell death has also been observed when CD16 + Mos were differentiated into M s [45] supports our conclusion that CD16 + Mos have a more activated phenotype.The relevance of the lack of CD1 molecules displayed by DCs derived from CD16 + Mos was supported by the association between the lower CD1b expression on DCs with their declined ability to present Mtb Ags [21]. In this line, it has been demonstrated that CD1-restricted T cells are expanded in TST + HSs and that CD1-restricted T-cell responses are absent or drastically reduced in TB patients [46], indicating an helpful role of CD1 molecules during Mtb infection.…”
supporting
confidence: 51%
“…Interestingly, since IL-1β has been described as an IL-12-inducing agent on human , the reduction of IL-1β + cells observed in CD16 + Mo-DCs could be associated with the low levels of IL-12 + cells. As TB patients have a high percentage of circulating CD16 + Mos [11,12], this dichotomy in the differentiation fate of Mo subsets can explain the impairment observed in Mo-derived DCs from TB patients [21]. In addition, we observed that CD16 + depletion in Mos from TB patients improved the differentiation toward DCs and that the addition of CD16 + Mos impaired the differentiation of Mos from HSs.…”
supporting
confidence: 48%
See 3 more Smart Citations